Successfully synthesis of FeSe2/CoFe2O4 heterojunction with high performance for hydrogen evolution reaction. (August 2020) - Zhang, Huixuan; Nengzi, Li-chao; Li, Bo; Cheng, Qingfeng; Gou, Jianfeng; Cheng, Xiuwen
Abstract: Water splitting related to renewable energy is considered to be one of the most important strategy for hydrogen production. In this article, highly active, durable, inexpensive and magnetic FeSe2 /CoFe2 O4 heterojunction was fabricated via a facile two-step hydrothermal method. Subsequently, the composite was characterized by a series of physicochemical technologies, including X-ray diffraction (XRD), scanning electron microscope (SEM), transmission electron microcopy (TEM), X-ray photoelectron spectra (XPS) and vibrating sample magnetometer (VSM) measurements. In order to evaluate the HER performance of the FeSe2 /CoFe2 O4 heterojunction, electrochemical measurements were also performed. Due to the unique band structure of FeSe2 nanorods and CoFe2 O4 nanoparticles and significant coupling effect between them, the FeSe2 /CoFe2 O4 heterojunction exhibited excellent HER activity with a small overpotential of 231 mV at a current density of 10 mA cm −2 . Besides, it had a smaller Tafel slope of 88.76 mV·dec −1 in acid media compared to single FeSe2 nanorods. At the same time, the heterojunction showed excellent mechanical stability with 9 h. Graphical abstract: Image 1 Highlights: FeSe2 /CoFe2 O4 was firstly fabricated via a facile two-step hydrothermal method. FeSe2 /CoFe2 O4 heterojunction exhibited excellent electrochemical performance. The excellent HER behavior was due to the unique structure of electrocatalyst.